2014
DOI: 10.1167/iovs.14-14958
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of Genetic Variants WithinTCF4in Fuchs' Endothelial Corneal Dystrophy

Abstract: Complete sequencing of the TCF4 genomic region revealed no single causative variant for FECD. The intronic trinucleotide repeat expansion within TCF4 continues to be more strongly associated with FECD than any other genetic variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 33 publications
1
17
0
5
Order By: Relevance
“…A similar situation was found in studies on the occurrence of FECD markers in the American population: In some studies, the ethnicity was not specified. 16,17,19,35 FECD patients hospitalized at the FEMCFSI are mostly from the Central, Southern, and Volga Federal Districts, and thus, these were included in our study. All of these Federal Districts are situated in the European part of Russia, so we specified that we investigated the occurrence of FECD markers in the background population of this part of Russia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar situation was found in studies on the occurrence of FECD markers in the American population: In some studies, the ethnicity was not specified. 16,17,19,35 FECD patients hospitalized at the FEMCFSI are mostly from the Central, Southern, and Volga Federal Districts, and thus, these were included in our study. All of these Federal Districts are situated in the European part of Russia, so we specified that we investigated the occurrence of FECD markers in the background population of this part of Russia.…”
Section: Discussionmentioning
confidence: 99%
“…Marker alleles were not found in 21 FECD patients; thus, exome sequencing for those particular patients is warranted. 18,19,22,35 76.4-77.0 21,26 17.3-34.1 37,40 43.9 41 25.5 42 72…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 A comprehensive assessment of 1866 genetic variants, with sequencing of the TCF4 coding region, introns, and flanking sequence surrounding the two variants, revealed that no single causative allele correlated with all cases of FCD, but the trinucleotide repeat is the most strongly associated of the two TCF4 variants. 45 Clusterin is a molecular chaperone which plays a role in extracellular matrix interaction and is overexpressed in FCD relative to pseudophakic bullous keratopathy and normal control corneas 46 and has been shown to colocalize in guttae. 47 In the aforementioned Australian cohort exploring association with TCF4, additional SNPs were interrogated and one found to be significant in CLU (rs17466684, p ¼ 0.003) with odds ratio of 1.85.…”
Section: Association Studiesmentioning
confidence: 99%
“…Um auszuschließen, dass die Repeat-Expansion und das G-Allel des Polymorphismus rs613872 in Kopplung mit einer Veränderung in codierenden Abschnitten des TCF4-Gens bzw. des ebenfalls nahe der untersuchten genetischen Region liegenden LOXHD1-Gens (das bei Riazuddin et al [12] [14,24,25]. Auch der Polymorphismus rs613872 ist mehrfach mit der Fuchs-Hornhautendotheldystrophie in Zusammenhang gebracht worden [15-18, 24, 25].…”
Section: Sequenzierung Tcf4 Und Loxhd1unclassified